1985
DOI: 10.3109/00016488509121766
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Morphology of the Mouse Inner Ear: A scanning electron microscopic observation

Abstract: The developing inner ears of mice (CBAKBA), ages ranging from gestational day 12 through postnatal day 21, were examined using scanning electron microscopy following the epoxy-embedding/ freeze-fracture technique. This technique provides unique three-dimensional views of surface and fractured structures of the developing inner ear, thus allowing excellent preservation of the relationships between the developing sensory epithelium and the overlying membranes (i.e. the tectorial membrane and cupula) during their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 59 publications
(33 reference statements)
11
145
2
Order By: Relevance
“…Others have reported that usherin disappears from the cochlear hair cells around postnatal day 15 (16). This transient expression pattern of usherin is correlated temporally with the maturation of stereocilia and the disappearance of the kinocilia (45). Furthermore, our study indicates that the hearing loss in the usherin mutant mice is nonprogressive.…”
Section: Discussionmentioning
confidence: 57%
“…Others have reported that usherin disappears from the cochlear hair cells around postnatal day 15 (16). This transient expression pattern of usherin is correlated temporally with the maturation of stereocilia and the disappearance of the kinocilia (45). Furthermore, our study indicates that the hearing loss in the usherin mutant mice is nonprogressive.…”
Section: Discussionmentioning
confidence: 57%
“…The inner ear is mature morphologically, and electrophysiologic properties of hair cells and gross cochlear response thresholds have stabilized by 4 weeks, the youngest animals studied here (Mikaelian et al, 1965;Lim and Anniko, 1985;Marcotti et al, 2003;Hafidi et al, 2005). Thresholds in the 8 -16 kHz range are almost identical in 4-versus 16-week-old animals (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…In situ hybridization of cochleae at E17 revealed that Dll3 follows the wave of hair cell differentiation (Lim and Anniko, 1985;Chen and Segil, 1999) and overlaps with expression of Dll1, Math1, and MyosinVIIa ( Fig. 3A-D,G-J).…”
Section: Dll3 Is Expressed In Developing Inner and Outer Hair Cells Imentioning
confidence: 99%